2020
DOI: 10.3390/ijerph17218119
|View full text |Cite
|
Sign up to set email alerts
|

What Socio-Economic and Political Factors Lead to Global Pesticide Dependence? A Critical Review from a Social Science Perspective

Abstract: Dependence on chemical pesticides has become one of the most pressing challenges to global environmental sustainability and public health. Considerable regulatory efforts have been taken to mitigate pesticide dependence, which however has resulted in a prevalent ‘managerial failure’. Massive pesticide application has generated severe genetic resistance from pests, which has in turn further aggravated pesticide dependence and thus induced agrochemical industries to develop new pesticide varieties. This review p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 110 publications
(312 reference statements)
1
20
0
Order By: Relevance
“…Farmers' use of pesticides should be based on knowledge and competence, and a lack of these skills can be a cause for the overuse of pesticides (Hu, 2020). Moreover, farmers may make ethical considerations that are be based on, for instance, the extent to which they believe the potential damage caused by pesticide use is acceptable (Sulemana & James, 2014).…”
Section: The Question Of Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Farmers' use of pesticides should be based on knowledge and competence, and a lack of these skills can be a cause for the overuse of pesticides (Hu, 2020). Moreover, farmers may make ethical considerations that are be based on, for instance, the extent to which they believe the potential damage caused by pesticide use is acceptable (Sulemana & James, 2014).…”
Section: The Question Of Responsibilitymentioning
confidence: 99%
“…This is done with scientific assessment studies that pesticide manufacturers have funded (Robinson et al, 2020). This position gives these manufacturers a strong responsibility in addition to the responsibility they have to provide label information regarding pesticide dosage for safe use (Hu, 2020).…”
Section: The Question Of Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides increase crop yields, minimize production costs, and enhance quality, thus increasing farmers' income. However, it has been found that the use of chemical insecticides is hazardous to human and animal health or the environment (Hu, 2020;Pazikowska-Sapota et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The case studies in Chapter 2 suggest that drivers from the 'science & technology' and 'society' domains can unlock the pesticide treadmill and initiated an 'escape & reorganization' phase in the past. While I have not been able to study drivers of these domains in detail, other scholars have focused on this (see e.g., Cowan and Gunby, 1996;Cowan and Hultén, 1996;Vanloqueren and Baret, 2008;Pretty and Bharucha, 2015;Boyd, 2018;Hu, 2020). For example, the technology lock-in of conventional pest management with synthetic pesticides has been compared to the adoption of alternative pest management options like Integrated Pest Management (IPM) (Cowan and Gunby, 1996).…”
Section: Social Lock-inmentioning
confidence: 99%